TO READERS OF DIGITAL TECHNOLOGIES INTERACTION (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article brings together a wide variety of technologies and methods of using platforms in the educational process. In addition, online platforms have been covered in detail about the interaction of the system with students in the educational process. There is also a brief comment on how and for what purpose to use MOOC-MOODLE, GOOGLE CLASSROOM and similar online platforms.